MINERALOGICAL COMPOSITION OF ELUVIAL-GLEY ZHELTOZEMS AS EXEMPLIFIED BY SOILS OF THE ARBORETUM IN SOCHI CITY - N. P. Chizhikova; I. A. Gurov (Бюллетень Почвенного института им. В.В. Докучаева)
The composition of fine-dispersed fractions (<1, 1-5 5-10 mkm) extracted from zheltozems located in the northern part of humid-subtropical zone in the North-Western Caucasus is represented by clay and accompanying minerals,  which have been fixed earlier in weathering crusts and their derivates characteristic of the given natural zone. The clay  fraction consists of a set of mixed-layer minerals, in which chlorite-vermiculite and mica-smectite are dominating within the soil profile. Hydromicas of dioctahedric type and kaolinite are subordinates. In the course of soil formation the  profile became differentiated according to the content of the fraction < 1 mkm and the composition of minerals in it. In the  eluvial part of the profile the individual smectite is absent but hydromicas, kaolinite, chlorite-vermiculite reveal  accumulation. Among destruction products the lepidocrocite is segregated in the AYEL horizon to a considerable extent.. The 1-5, 5-10 mkm fractions are evenly distributed, quartz is dominated.